Revolutionary Approaches to Hair Regrowth: Follicle Neogenesis, Wnt/ß-Catenin Signaling, and Emerging Therapies - Apoorva Mehta; Mateen Motavaf; Danyal Raza; Alison J. McLure; Kofi D. Osei-Opare; Lindsey A. Bordone; Alejandro A. Gru (Cells)
With alopecia affecting millions globally, recent advancements in the understanding of hair follicle biology have driven the development of novel therapies focused on hair regrowth. This review discusses two emerging therapeutic strategies: hair follicle neogenesis and the modulation of the Wnt/B-catenin signaling pathway. Hair follicle neogenesis, a frontier once considered impossible to achieve in adult humans, has recently gained traction due to advancements in stem cell biology and further understanding of the epithelial–mesenchymal interactions that are critical to hair follicle development. Such an approach shows significant potential for addressing conditions leading to hair loss, such as androgenetic and scarring alopecias. The Wnt/B-catenin signaling pathway, a critical intracellular pathway responsible for hair follicle cycles, has gained traction as a target for therapeutic interventions. Studies show that stimulating this pathway leads to hair follicle growth, while its inhibition prompts hair follicle regression. Investigations demonstrate clinical efficacy of small molecule inhibitors and peptides, such as PTD-DBM, which activates the Wnt/β-catenin pathway by interfering with CXXC5, a negative regulator that inhibits pathway activation. Such therapies show potential as more effective treatment options than existing solutions such as finasteride and minoxidil. Adjunctive therapies, such as low-level laser therapy, have also shown clinical efficacy, further highlighting how modulation of this pathway stimulates follicular regrowth. While these novel therapies require further research to validate their efficacy and to gain additional insight into their risk profile, it is clear that alopecia treatment is approaching a new frontier beyond traditional pharmacologic interviews, with regenerative medicine and pathway modulation paving the way forward.